ANALISIS IMPLEMENTASI SISTEM DATA PILAH GENDER DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Syahriza, Rahmi; Nashrillah MG, Nashrillah MG; Nurasiah, Nurasiah (Kafa`ah: Journal of Gender Studies, 2023)
The realization of Gender Responsive Budgeting Planning (PPRG) is supported by the existence of a gender disaggregated data system in a university. This study aims to determine the implementation and effectiveness of the gender disaggregated data system at the State Islamic University of North Sumatra. This research is a qualitative research. Data was collected by means of in-depth interviews with the University, all faculties, and the Information Center and UIN North Sumatra Database. The results showed that the gender disaggregation data system had not been fully implemented by UIN North Sumatra. Although in practice, gender justice has been carried out quite maximally with the opportunities given to lecturers and education staff who occupy strategic positions at UIN North Sumatra. The existence of the Center for Gender and Child Studies at UIN North Sumatra also plays a significant role with the dissemination of the Gender Based System (GBS) and Gender Analysis Pathway (GBP), but the implementation and development of an integrated gender disaggregation data system is still not effective. This is due to the coordination has not been optimal in all lines and units on campus, and there are still no policies and regulations related to the legality of an integrated and interconnected gender disaggregated data system at UIN North Sumatera.Terwujudnya Perencanaan Penganggaran Responsif Gender (PPRG) didukung dengan adanya sistem data pilah gender di sebuah perguruan tinggi. Penelitian ini bertujuan untuk mengetahui implementasi dan efektivitas sistem data pilah gender di Universitas Islam Negeri Sumatera Utara. Penelitian ini adalah penelitian kualitatif. Data dikumpulkan dengan metode wawancara mendalam kepada pihak Universitas, semua fakultas, dan bagian Pusat Informasi dan pangkalan Data UIN Sumatera Utara. Hasil penelitian menunjukkan bahwa sistem data pilah pilah gender belum sepenuhnya diterapkan oleh UIN Sumatera Utara. Meskipun dalam prakteknya, keadilan gender sudah dilaksanakan cukup maksimal dengan adanya kesempatan yang diberikan kepada tenaga pendidik dan tenaga kependidikan yang menduduki jabatan strategis di UIN Sumatera Utara. Keberadaaan Pusat Studi Gender dan Anak yang ada di UIN Sumatera Utara juga memberikan peran yang cukup besar dengan dilakukannya sosialisasi Gender Based System (GBS) dan Gender Analysis Pathway (GBP), tetapi pelaksanaan dan pembuatan sistem data pilah gender yang terintegrasi masih belum efektif. Hal ini karena koordinasi yang belum masksimal di semua lini dan unit yang ada di kampus, kemudian juga masih belum adanya kebijakan dan regulasi terkait legalitas sistem data pilah gender yang terintegrasi dan terinterkoneksi di UIN Sumatera Utara